PENGARUH INPUT DAN PROSES TERHADAP PRODUK PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMK MUHAMMADIYAH PURWOREJO - Shakira Khalyana Pallaz Athena; Sugeng Eko Putro Widoyoko; Cahyo Apri Setiaji (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to analyze the influence of input and process on the P5 product at SMK Muhammadiyah Purworejo. The urgency of this research lies in the importance of evaluating the implementation of the P5 project as part of the Merdeka Curriculum, which focuses on developing students’ character and competencies. The research method employed is an evaluative study with a quantitative approach, utilizing the CIPP (Context, Input, Process, Product) evaluation model. The sample consisted of 58 students selected from a population of 71 eleventh-grade students using the proportional random sampling technique. This method ensures that the sample selection is representative, with the number of subjects proportionally determined for each class. Data were collected through questionnaires, interviews, and document analysis, then analyzed using descriptive and inferential statistics. The results indicate that the input and process variables simultaneously influence the P5 product, with R = 0.797, Fcount = 47.839, and a significance value of 0.000. Future studies are recommended to include the context aspect to make the evaluation of P5 implementation more comprehensive and sustainable.